Controlling RNA self-assembly to form filaments - Nasalean, Lorena (Oxford University Press, 2006)
Fundamental control over supra-molecular self-assembly for organization of matter on the nano-scale is a major objective of nanoscience and nanotechnology. ‘RNA tectonics’ is the design of modular RNA units, called tectoRNAs, that can be programmed to self-assemble into novel nano- and meso-scopic architectures of desired size and shape. We report the three-dimensional design of tectoRNAs incorporating modular 4-way junction (4WJ) motifs, hairpin loops and their cognate loop–receptors to create extended, programmable interaction interfaces. Specific and directional RNA–RNA interactions at these interfaces enable conformational, topological and orientational control of tectoRNA self-assembly. The interacting motifs are precisely positioned within the helical arms of the 4WJ to program assembly from only one helical stacking conformation of the 4WJ. TectoRNAs programmed to assemble with orientational compensation produce micrometer-scale RNA filaments through supra-molecular equilibrium polymerization. As visualized by transmission electron microscopy, these RNA filaments resemble actin filaments from the protein world. This work emphasizes the potential of RNA as a scaffold for designing and engineering new controllable biomaterials mimicking modern cytoskeletal proteins.